Phalaropus fulicarius ... - Boano, Giovanni; Belemsobgo, Urbain; Silvano, Fabrizio; Hema, Emmanuel M.; Belemsobgo, Aristide; Dimobe, Kangbéni; Pavia, Marco (Zenodo, 2022)
Phalaropus fulicarius (Linnaeus, 1758) LITERATURE. — Pavia et al. (2012); Borrow & Demey (2014), STATUS. — Palaearctic vagrant. REMARK. — First record of the species for Burkina Faso documented by Pavia et al. (2012) at Moussodougou Lake, Cascade Region, 16.II.2010. ... : Published as part of Boano, Giovanni, Belemsobgo, Urbain, Silvano, Fabrizio, Hema, Emmanuel M., Belemsobgo, Aristide, Dimobe, Kangbéni & Pavia, Marco, 2022, An annotated checklist of the birds of Burkina Faso, pp. 27-107 in Zoosystema 44 (2) on page 52, DOI: 10.5252/zoosystema2022v44a2, http://zenodo.org/record/5999691 ...